SURVEI KEBERADAAN SERANGGA Cimex sp PADA LINGKUNGAN RUMAH TANGGA DIKAITKAN DENGAN KADAR HEMOGLOBIN PENGHUNI RUMAH DI DESA GEBANG SUKODONO SRAGEN - Didik Sumanto; Fuad Alhamidy (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Background : Cimex sp is a blood sucking insects that allow for continuous blood loss for men who always contact every day so it is possible to make the condition of anemia. Objective : To survey the presence of Cimex sp and measuring the gweller hemoglobin levels and analyzes the relationship between the two. Research method : Analytical research with survey method and using cross sectional approach.Result : Found Cimex sp in 70% (21 houses) of respondent and respondents with less than normal hemoglobin of 66.7% (20 persons). Conclusion : There is a relationship between the presence of Cimex sp with hemoglobin (Hb) levels of respondents Key words : survey, Cimex sp, hemoglobin